Understanding the behavior of mixtures of protic-aprotic and protic-protic ionic liquids: conductivity, viscosity, diffusion coefficient and ionicity - Thawarkar, S.; Khupse, N. D.; Shinde, D. R.; Kumar, A. (Journal of Molecular Liquids, 2019)
We have investigated the physicochemical properties such as electrical conductivity, viscosity and diffusion coefficient for the binary mixtures of protic ionic liquids with aprotic ionic liquids and of protic with protic ionic liquids at 298.15 K. A significant enhancement in the electrical conductivity is observed for the binary mixtures of ionic liquids, as compared to those of the constituent pure ionic liquids and varied with the composition of the mixtures. The viscosity of binary mixtures of protic with aprotic ionic liquids, 1‑butyl‑3‑methylimidazoliumbis(trifluoromethylsulfonyl)imide [bmIm][NTf2], 1‑butyl‑1‑methylpyrrolidiumbis(trifluoromethylsulfonyl)imide [bmPyrr][NTf2] and 1,3-dimethylimidazolium methyl sulfate, [mmIm][CH3SO4] decreases with an increase in the composition of the [HmIm][CH3COO]. On the contrary, the viscosity for binary mixtures of protic with protic ionic liquid, 1‑methylpyrrolidium acetate [HmPyrr][CH3COO] and 4‑methylmorpholine acetate [HmMorph][CH3COO] increases upon the addition of 1‑methylimidazolium acetate [HmIm][CH3COO]. The self diffusion coefficients were determined for all the binary mixtures of ionic liquids by using Pulsed Gradient Spin Echo (PGSE) NMR method. Self diffusion coefficients of [bmIm][NTf2]-[HmIm][CH3COO], [bmPyrr][NTf2]-[HmIm][CH3COO], [mmIm][CH3SO4]-[HmIm][CH3COO] are enhanced, while those of [HmPyrr][CH3COO]-[HmIm][CH3COO] and [HmMorph][CH3COO]-[HmIm][CH3COO] decreases on addition of [HmIm][CH3COO]. This is converse in the case of viscosity. Furthermore, the above correlations were interpreted with the help of NMR spectroscopy on the basis of interactions of ions in the binary mixtures of ionic liquids. Finally, we have quantified the ionicity through the Nernst–Einstein equation and have confirmed the validity of the Walden rule for the binary mixture of ionic liquids.